Strategic analysis and growth in an emerging economy (A) : mobile handset industry in India - Salwan, Prashant (SAGE Knowledge. Cases., 2009)
This is the first case in the series on strategic analysis and growth in an emerging economy. In case A Nokia is the market leader in India's mobile handset market. Until 2001 Nokia had not experienced competition in this market. After 2003 there were four additional major competitors in the market: Samsung, Sony Ericsson, LG and other local manufactures. Nokia's market share was falling. India is an emerging economy, which is growing at an exceptional growth rate. The demographics, legal system, and economy are all very dynamic and important opportunities for mobile handset manufactures are presenting themselves. External forces as well as industry forces are changing very rapidly. The MDs of the mobile handset manufacturers are planning their future strategies in India.